2020
DOI: 10.21608/jpp.2020.118024
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Stability of some Bread Wheat Genotypes across Terminal Water and Heat Stresses Combinations Using Biplot Techniques

Abstract: The current study was conducted at Shandaweel Agric. Res. Stat., Agric. Res. Center, Egypt. Eighteen bread wheat genotypes were grown under four treatments during 2018/19 and 2019/20 seasons. The treatments were (1) normal conditions (sowing on 25 th November and 5 irrigations). (2) Terminal water stress conditions (sowing on 25 th November and 3 irrigations). (3) Terminal heat stress conditions (sowing on 25 th December and 4 irrigations). (4) Combined stresses (sowing on 25 th December and 3 irrigations). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…Results showed that full irrigation (100%) treatment produced the highest values of all studied traits, followed by irrigation regime 60% then irrigation with 40% of full irrigation. Similar results were obtained by Feltaous and Koubisy (2020). They declared a high reduction for most agronomic traits as a result of terminal water stress conditions.…”
Section: Effect Of Irrigation Treatmentssupporting
confidence: 83%
See 2 more Smart Citations
“…Results showed that full irrigation (100%) treatment produced the highest values of all studied traits, followed by irrigation regime 60% then irrigation with 40% of full irrigation. Similar results were obtained by Feltaous and Koubisy (2020). They declared a high reduction for most agronomic traits as a result of terminal water stress conditions.…”
Section: Effect Of Irrigation Treatmentssupporting
confidence: 83%
“…On the other hand, the worst cultivar was Sids 14 for grain yield, Sids 14 and Shandaweel 1 for biological yield, Giza 171 for harvest index % under all irrigation treatments. According to the previous studies, the genotypes behaved differently under irrigation treatments across different seasons (Farhat, 2015, Feltaous and Koubisy, 2020.…”
Section: Interaction Between Irrigation Treatments and Cultivarsmentioning
confidence: 90%
See 1 more Smart Citation
“…If the genotypes are evaluated based on the combination of traits and yield obtained from multiple locations, they will be very stable in all traits and yield across similar environments. For this reason, the GYT biplotting technique is used by some researchers to evaluate the performance of combining multiple traits with yield and multiple environments in breeding research [46,47]. Certain agronomic traits (GWE, ED, EL, and PH) directly increase the grain yield, while some agronomic traits directly reduce grain yield, such as LR, BTL and GP.…”
Section: Correspondence Among the Stability Indexesmentioning
confidence: 99%
“…Except for grain density in PKV Kranti × DSMR4, the entire studied trait's scaling test values were found to be significantly different from zero, indicating the presence of nonallelic gene interaction and the inadequacy of the additive dominance model for the inheritance of these traits (Table 2). Whereas, for the grain density in the cross PKV Kranti × DSMR4 the additive dominant model was found to be adequate [7,8].…”
Section: Adequacy Of Additive-dominance Modelmentioning
confidence: 86%